Synthesis and Antifungal Activity of Some Bis-Heterocycles Derived from Hydroquinone, Part-I - Joshi, P.C.; Rautela, R. (Asian Journal of Chemistry, 2010)
In the present work the synthesis of some new bis-1,4-(5-arylamino-2-oxymethyl-1,3,4-thiadiazol-2-yl) benzenes and bis-1-4-(3-mercapto-4-aryl-5-oxymethyl-1,2,4-triazol-5-yl) benzenes were synthesized and werescreneed for their antifungal activity.